A STUDY OF ORGANIZATIONAL PRACTICES OF CSR - AN INSIGHT FROM MANUFACTURING INDUSTRY - Nasreen, Dr. Asiya; Anjum, Rifat (Innovare Journal of Social Sciences, 2017)
The scope of Corporate social responsibility (CSR) has enlarged the role that manufacturing industries could play today for societal development. Manufacturing industries since their inception have made a tremendous impact on a country's economy. Being the second largest contributor in Indian economy, an unsaid obligation lies within them to help the community prosper. The research paper looks into the CSR practices carried out by two large scale manufacturing industries located in the north agrarian belt of India. The challenges in implementation of CSR activities have been understood to provide recommendations for the same. The findings reinforce the fact that manufacturing industries are tremendously contributing towards the community in which they operate and is concluded by recommending on the need to increase the acceptance level by the community in which these industries operate